Mammalian cell lines expressing functional RNA polymerase II tagged with the green fluorescent protein. - Sugaya, K; Vigneron, M; Cook, P (2000)
RNA polymerase II is a multi-subunit enzyme responsible for transcription of most eukaryotic genes. It associates with other complexes to form enormous multifunctional 'holoenzymes' involved in splicing and polyadenylation. We wished to study these different complexes in living cells, so we generated cell lines expressing the largest, catalytic, subunit of the polymerase tagged with the green fluorescent protein. The tagged enzyme complements a deficiency in tsTM4 cells that have a temperature-sensitive mutation in the largest subunit. Some of the tagged subunit is incorporated into engaged transcription complexes like the wild-type protein; it both resists extraction with sarkosyl and is hyperphosphorylated at its C terminus. Remarkably, subunits bearing such a tag can be incorporated into the active enzyme, despite the size and complexity of the polymerizing complex. Therefore, these cells should prove useful in the analysis of the dynamics of transcription in living cells.